Pentingnya User Experience Dalam Mengenalkan Home Greeneries ke Masyarakat Urban - Steven Renaldo Hartono; Shienny Sutanto (Jurnal Vicidi, 2017)
This research is aimed to fullfill the assignment of Visual Communication Design using the development of entrepreneurship through a business engaged in home greeneries, namely home decor that has elements of living plants in it such as succulent, cactus, fern, living moss, and others. This paper will describe the research process and influence of user experience in introducing a greeneries product to a target market. The purpose of making this business idea itself stems from the observation about the lack of living plant presence in a residence or work environment. The research used qualitative methods. Qualitative methods are carried out through interviews and workshops in the form of a market test. Result of this research is that the presence of living plant is important, but required a clear user experience to be able to introduced to the urban society.